2007
DOI: 10.1562/0031-8655(2001)0740670coddpb2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA Damage Photoinduced by Ketoprofen, Fenofibric Acid and Benzophenone via Electron and Energy Transfer¶

Abstract: Ketoprofen (KP) and fenofibrate, respectively, anti-inflammatory and hypolipidemiant agents, promote anormal photosensitivity in patients and may induce photoallergic cross-reactions correlated to their benzophenone-like structure. Here, their ability to photosensitize the degradation of biological targets was particularly investigated in DNA. The photosensitization of DNA damage by KP and fenofibric acid (FB), the main metabolite of fenofibrate, and their parent compound, benzophenone (BZ), was examined on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
11
0
1
Order By: Relevance
“…The cutaneous phototoxicity is a common health problem caused by the interaction of sunlight and drugs are absorbed either locally into the skin or via the systemic circulation and become the substrate for photochemical reactions in the skin (33). Previous studies have shown that low to moderately pigmented human skin may be vulnerable to phototoxic effects (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous phototoxicity is a common health problem caused by the interaction of sunlight and drugs are absorbed either locally into the skin or via the systemic circulation and become the substrate for photochemical reactions in the skin (33). Previous studies have shown that low to moderately pigmented human skin may be vulnerable to phototoxic effects (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…To prepare first strand cDNA, 1 mg of RNA was incubated in 100 ml of buffer containing 10 mM dithiothreitol, 2.5 mM MgCl 2 , dNTP mix, 200 U of reverse transcriptase II (Invitorogen, Carlsbad, CA, USA) and 0.1 mM oligo (dT) [12][13][14][15][16][17][18] (Invitorogen). To prepare first strand cDNA, 1 mg of RNA was incubated in 100 ml of buffer containing 10 mM dithiothreitol, 2.5 mM MgCl 2 , dNTP mix, 200 U of reverse transcriptase II (Invitorogen, Carlsbad, CA, USA) and 0.1 mM oligo (dT) [12][13][14][15][16][17][18] (Invitorogen).…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr) Assaymentioning
confidence: 99%
“…In addition to the high incidence of occurrence of photocontact dermatitis, KP is an interesting drug in its cross-photoreactivity with thiaprofenic acid, suprofen, phenofibrate, and benzophenone-3 [7][8][9][10][11]. These substances have a photohaptenic moiety [2] as well as a phototoxic ability [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of pharmacology, their photostability, photochemistry and phototoxicity are key factors. Many NSAIDs contain a chromophore such as naphthalene and benzophenone, and can undergo photosensitization reaction that would give rise to undesired phototoxic and photoalleregic effects on human skin (1)(2)(3)(4)(5)(6)(7)(8). The information on the photoreaction mechanism of NSAIDs should be required to understand their photosensitization on human skin.…”
Section: Introductionmentioning
confidence: 99%